2015
DOI: 10.1038/ncomms8771
|View full text |Cite
|
Sign up to set email alerts
|

Atomic view of the histidine environment stabilizing higher-pH conformations of pH-dependent proteins

Abstract: External stimuli are powerful tools that naturally control protein assemblies and functions. For example, during viral entry and exit changes in pH are known to trigger large protein conformational changes. However, the molecular features stabilizing the higher pH structures remain unclear. Here we elucidate the conformational change of a self-assembling peptide that forms either small or large nanotubes dependent on the pH. The sub-angstrom high-pH peptide structure reveals a globular conformation stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
(53 reference statements)
5
37
0
Order By: Relevance
“…Conversely, at increasing pH-values, histidine loses one proton in its imidazole ring, which gradually gives rise to neutral forms ( Figure 9D). Valery et al (2015) studied the conformational change of self-assembled histidine-containing peptides and their stabilized globular conformation at high pH. Vibrational spectroscopy assessments revealed histidineserine H-bond and histidine-aromatic interactions.…”
Section: Interpretation Of the Raman Analysesmentioning
confidence: 99%
“…Conversely, at increasing pH-values, histidine loses one proton in its imidazole ring, which gradually gives rise to neutral forms ( Figure 9D). Valery et al (2015) studied the conformational change of self-assembled histidine-containing peptides and their stabilized globular conformation at high pH. Vibrational spectroscopy assessments revealed histidineserine H-bond and histidine-aromatic interactions.…”
Section: Interpretation Of the Raman Analysesmentioning
confidence: 99%
“…The rational design and usage of defined amyloid‐based nanostructures are still being hindered by several issues, which include the high aggregation propensity of amyloidogenic β‐sheet‐forming sequences, the lack of control over the self‐assembly process and the difficulty of predicting the final supramolecular architecture from the primary sequence . In contrast to polymers built on covalent bonds, bottom‐up polypeptide amyloid self‐assembly relies on the formation of a complex and organized network of intermolecular noncovalent interactions .…”
Section: Introductionmentioning
confidence: 99%
“…The second technique was based on a recent study of Valery et al ., which showed that a change of pH value and thus deprotonation of the His residue in the GnRH agonist, TRH, could trigger a self-assembly of the peptide into nanotubes 22 . This pH dependent switch can be applied in the bottom-up development of pH-responsive nanomaterials as well as for the in vitro induced conformational change and fibrillation of GnRH [6-D-Phe].…”
Section: Resultsmentioning
confidence: 99%